Increased adhesive potential of antiphospholipid syndrome neutrophils mediated by beta-2 integrin Mac-1 - Sule, Gautam (Arthritis Rheumatol, 2020)
OBJECTIVE: While the role of antiphospholipid antibodies in activating endothelial cells has been extensively studied, the impact of these antibodies on the adhesive potential of leukocytes has received less attention. Here, we investigated the extent to which antiphospholipid syndrome (APS) neutrophils adhered to resting endothelial cells under physiologic flow conditions, as well as the surface molecules required for that adhesion. METHODS: Patients with primary APS (n=43), patients with history of venous thrombosis but negative testing for antiphospholipid antibodies (n=11), and healthy controls (n=38) were studied. Cells were introduced into a flow chamber and perfused across resting human umbilical vein endothelial cell (HUVECs). Surface adhesion molecules were quantified by flow cytometry. Neutrophil extracellular trap (NET) release (NETosis) was assessed in neutrophil-HUVEC co-cultures. RESULTS: Upon perfusion of anticoagulated blood through the flow chamber, APS neutrophils demonstrated increased adhesion as compared with control neutrophils under conditions representative of either venous (n=8, p<0.05) or arterial (n=15, p<0.0001) flow. At the same time, APS neutrophils were characterized by upregulation of CD64, CEACAM1, beta-2 glycoprotein I, and activated Mac-1 on their surface (n=12–18, p<0.05 for all markers). Exposing control neutrophils to APS plasma or APS IgG resulted in increased neutrophil adhesion (n=10–11, p<0.001) and surface marker upregulation as compared with controls. A monoclonal antibody specific for activated Mac-1 reduced the adhesion of APS neutrophils in the flow-chamber assay (p<0.01). The same monoclonal antibody reduced NETosis in neutrophil-HUVEC co-cultures (p<0.01). CONCLUSION: APS neutrophils demonstrate increased adhesive potential, which is dependent upon the activated form of Mac-1. In patients, this could lower the threshold for neutrophil-endothelium interactions, NETosis, and possibly thrombotic events.